2011
DOI: 10.1364/oe.19.016985
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient THG in TiO_2 nanolayers for third-order pulse characterization

Abstract: Third harmonic generation (THG) of femtosecond laser pulses in sputtered nanocrystalline TiO2 thin films is investigated. Using layers of graded thickness, the dependence of THG on the film parameters is studied. The maximum THG signal is observed at a thickness of 180 nm. The corresponding conversion efficiency is 26 times larger compared to THG at the air-glass interface. For a demonstration of the capabilities of such a highly nonlinear material for pulse characterization, third-order autocorrelation and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…These studies were now also extended to TiO 2 . For TiO 2 layers with nanogranular surfaces, a significant enhancement of third harmonic generation was reported [13]. Currently, the specific mechanisms of such surface enhanced nonlinear processes are still not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were now also extended to TiO 2 . For TiO 2 layers with nanogranular surfaces, a significant enhancement of third harmonic generation was reported [13]. Currently, the specific mechanisms of such surface enhanced nonlinear processes are still not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Both LSFLs and HSFLs were observed in the fs laser ablation of Ti [6,22,23]. In particular, the shortest period of HSFLs was found to be only one-tenth of the irradiation laser wavelength and the physical mechanism responsible for the deep subwavelength period is still under investigation [22][23][24][25][26][27]. In fact, sub-100-nm HSFLs have been demonstrated in the ablation of Ti by using 790-nm fs laser pulses and it was suggested that laser-induced oxide (i.e., the formation of TiO 2 on the surface of Ti) might play an important role in the formation of such HSFLs [22].…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of such pulses is rendered complex by the ultrashort, broadband, nature of such pulses (> 100 nm) where dispersive effects can be dominant and thus one needs extremely thin nonlinear crystals for faithful pulse characterization [8]. Recently our group has demonstrated the use of TiO 2 nanocrystalline thin films to characterize pulses as short as 20 fs, demonstrating the utility of nanostructured metal oxides for such applications, where the nano length scales allow one to avoid phase-matching constraints associated with traditional bulk nonlinear materials [9].…”
Section: Introductionmentioning
confidence: 99%